Pengaruh Posisi pada Batang terhadap Sifat Fisik dan Dimensi Serat Kayu Gmelina Hasil Penjarangan (The Influence of Stem Position on Physical Properties and Fiber Dimension of Gmelina from Thinning Activity) - Sigit B Prabawa (Masyarakat Peneliti Kayu Indonesia, 2017)
Gmelina arborea Roxb. is a native species to Bangladesh, Cambodia, Southern China, India, Japan, Laos, Myanmar, Nepal, Pakistan, Sri Lanka, Thailand, Vietnam, and Indonesia. Its regional name includes Gamar, Yemane, Khamari, White Teak, Gmelina, and Melina. For commercial purposes, gmelina can be reasonably developed for industrial forest plantation or community forest plantation in Indonesia based on its wood characteristics. The objectives of this study were to determine the physical properties and fiber dimension of wood procured from thinning activities. The research showed that the oven and air dried density, air dried specific garvity, and air dried moisture content of the gmelina wood were 0.38 g cm-3, 0.44 g cm-3, 0.37 and 19.82% respectively. The average of the fiber length, fiber diameter, lumen diameter and cell wall thickness were 820.13, 27.16, 21.13, and 3.01 µm, respectively. The differences in position on the stem affect the density, specific gravity and fiber length, in which the higher position of the stem, the lower of their values. But it does not affect the air dry water content, the fiber diameter, lumen diameter and cell wall thickness.Keywords: fiber dimension, Gmelina arborea, physical properties, thinning, wood utilization